Mouse Sperm Cryopreservation and Recovery using the I·Cryo Kit - Liu, Ling (MyJove Corporation, 2011)
Thousands of new genetically modified (GM) strains of mice have been created since the advent of transgenesis and knockout technologies. Many of these valuable animals exist only as live animals, with no backup plan in case of emergency. Cryopreservation of embryos can provide this backup, but is costly, can be a lengthy procedure, and generally requires a large number of animals for success. Since the discovery that mouse sperm can be successfully cryopreserved with a basic cryoprotective agent (CPA) consisting of 18% raffinose and 3% skim milk, sperm cryopreservation has become an acceptable and cost-effective procedure for archiving, distributing and recovery of these valuable strains. Here we demonstrate a newly developed I•Cryo kit for mouse sperm cryopreservation. Sperm from five commonly-used strains of inbred mice were frozen using this kit and then recovered. Higher protection ratios of sperm motility (> 60%) and rapid progressive motility (> 45%) compared to the control (basic CPA) were seen for sperm frozen with this kit in 5 inbred mouse strains. Two cell stage embryo development after IVF with the recovered sperm was improved consistently in all 5 mouse strains examined. Over a 1.5 year period, 49 GM mouse lines were archived by sperm cryopreservation with the I•Cryo kit and later recovered by IVF.